Training exercises, match demands, and variability in elite futsal - Ribeiro, J. N.; Ferraz, A.; Gonçalves, B.; Serrano, C.; Coutinho, D.; Ballester, R.; Travassos, B. (Frontiers in Sports and Active Living, 2025)
Introduction: Understanding the physical demands of different training exercises is crucial for optimizing athlete performance. This study aims to compare high-intensity activities across different training exercises and official match-play scenarios. The analysis focuses on performance variations across training exercises and the variability observed within each format.